The Symbol of the Phoenix in the Catacombs of Priscilla in Rome and Its Transformation in Early Christianity - Kardis, Mária; Tlučková, Dominika (The Biblical Annals, 2022)
The presented study deals with the oldest Christian depiction of a phoenix found in the Catacombs of Priscilla in Rome. Since catacomb art is a narrative depiction of biblical stories, it is important to incorporate the motive of phoenix into historical context. The study performs analysis and comparison the links and connections of the phoenix symbol in pagan and Christian thought. As Christian iconography is associated with allegorical symbols, the intention is to anticipate the meaning, origin and etymology of the phoenix symbol. The article therefore summarizes how the symbol and position of the phoenix found in the catacombs evolved from Egyptian myths through Greek and Roman culture to the transformation in Christian literature and Christian thought, especially in the Gospel of John, which connects the symbol of the phoenix with the palm and Lazarus.